1992
DOI: 10.1073/pnas.89.8.3635
|View full text |Cite
|
Sign up to set email alerts
|

Calcium uptake in the skin of a freshwater teleost.

Abstract: The skin, particularly the opercular membrane of some teleosts, contains mitochondrion-rich "chloride" cells and has been widely used as a model to study branchial salt-extrusion mechanisms in seawater fish. Skin isolated from the operculum of the freshwater Nile tilapia (Oreochromis nilotcus) can transport Ca2' against an ionic and electrical gradient. Adaptation of Nile tilapia to a low-Ca21 environment increased the capacity ofthe opercular membrane to transport Ca2+. The density of mitochondrion-rich cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(79 citation statements)
references
References 30 publications
1
76
2
Order By: Relevance
“…opercular membrane; McCormick et al 1992, Marshall et al 1992 and from the diet via the intestine. In the present study, we aimed to determine the contribution of the intestine to calcium regulation since marine fish drink large amounts of seawater (containing 10 mmol/l calcium in our experiments) and the intestine is known to play an important role in osmoregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…opercular membrane; McCormick et al 1992, Marshall et al 1992 and from the diet via the intestine. In the present study, we aimed to determine the contribution of the intestine to calcium regulation since marine fish drink large amounts of seawater (containing 10 mmol/l calcium in our experiments) and the intestine is known to play an important role in osmoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the calcium transport mechanisms are proposed to take place actively at the level of the gills (Flik et al 1995) and, at least in some species, partly through the skin (McCormick et al 1992, Marshall et al 1992. In fresh water, fish drink very little and as a consequence virtually all the calcium incorporated via the intestine is of dietary origin.…”
Section: Introductionmentioning
confidence: 99%
“…The gills are considered to account for a large part of the calcium uptake by freshwater fish (Mashiko and Jozuka, 1962;Perry and Wood, 1985;Flik et al, 1985a), and active calcium uptake mechanisms have been demonstrated in the gills of several teleost species (Flik et al, 1984(Flik et al, , 1985bFlik and Perry, 1989). Further, some environmental calcium uptake can occur across skin and fins (Mashiko and Joshuka, 1962;Perry and Wood, 1985), and it has been shown that teleost skin is capable of active calcium uptake, with the calcium transporting capacity increasing with the density of mitochondriarich cells (Marshall et al, 1992;McCormick et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of human colonic epithelium, a reduction in water Ca 2 þ concentration ([Ca 2 þ ]) increases NaR cell number on the yolk sac skin in zebrafish embryos and larvae. 11 In fact, acclimation to low [Ca 2 þ ] has been shown to increase ionocyte number and/or density in the adult gills in many teleost species for more than two decades, 12,13 suggesting an evolutionarily conserved regulatory mechanism at work.…”
mentioning
confidence: 99%